2008
DOI: 10.1007/s00259-008-0752-y
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide scintigraphy in the evaluation of gastroesophageal reflux in symptomatic and asymptomatic pre-term infants

Abstract: GER is common in pre-term infants of less than 34 weeks gestation. The incidence of positive scintigraphy and grade of reflux is not significantly different in symptomatic vs. asymptomatic babies. Though radionuclide scintigraphy is a simple, quick and non-invasive investigation in suspected cases of GER, positive scintigraphy has no correlation with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In the literature, previous studies mentioned about relationship between reflux scintigraphy and clinical symptoms and role of the reflux in etiology of respiratory disease [3, 5]. According to our knowledge, although it is well known that growth and development are affected by clinically [3, 12-15].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, previous studies mentioned about relationship between reflux scintigraphy and clinical symptoms and role of the reflux in etiology of respiratory disease [3, 5]. According to our knowledge, although it is well known that growth and development are affected by clinically [3, 12-15].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of evidence regarding the determination of lipid-laden macrophages (LLM) in BAL resulted in the conclusion that this method lacks sensitivity and specificity [1]. More recent data show the presence of pepsin in BAL and middle ear fluid [1,74]. Also, bile salts are detected in middle ear fluid [80].…”
Section: Diagnosismentioning
confidence: 97%
“…One study evaluating nuclear scintigraphy with late imaging reported that 50 % of the patients with a variety of respiratory symptoms had pulmonary aspiration after 24 h [73]. However, later studies failed to reproduce these findings [74]. Aspiration also occurs in healthy subjects, especially during sleep [1].…”
Section: Ger(d) and Recurrent Pneumoniamentioning
confidence: 98%
“…GERD is considered common in premature infants younger than 34 weeks gestational age, but the severity of GERD is not significantly different in symptomatic and asymptomatic infants [37,40,50]. Some authors stated that GERD is common even in premature infants younger than 32 weeks gestational age [33,34,36,41,44].…”
Section: The Age Of the Premature Child When The Pattern Of Gerd Can mentioning
confidence: 99%
“…Other frequently documented symptoms of GERD were: coughing, "grunting" (labored breathing), recurrent attacks with cyanosis, arching, grimacing, crying, showing signs of irritability, discomfort and pain, and stretching out extremities [37][38][39][40]. Other studies describe some of these symptoms as not so common/more rare, like difficulty gaining weight/failure to thrive, desaturation, "choking", "gagging", chewing, refusing to eat, irritability, showing discomfort, grimacing, and arching, cough, yawning, hiccups and sneezing [41,42].…”
Section: Specific Symptoms Of Gerd In Premature Infantsmentioning
confidence: 99%